Ondansetron as the first approach in the management of the patients with acute gastroenteritis visiting the pediatric emergency department: A single-center experience - Pierluigi Marzuillo; Erica Vecchione; Carolina DAnna; Vincenzo Tipo (Turkish Journal of Gastroenterology, 2019)
-